PENGARUH LEADERSHIP DAN COMMUNICATION TERHADAP PERFORMANCE EMPLOYEE PADA PT. ISS INDONESIA SUKOREJO PASURUAN - Prabowo, Bahtiar (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
The purpose of this study was to determine the significant effect of leadership and communication styles on employee performance. The population in this study was 140 people, and samples were taken using purposive sampling with the criteria of group C employees as many as 35 people. The analytical analysis used is multiple linear regression. The results of this study shown that the coefficient of determination (R2) are 0.915, this mean that 91.5% of the performance variables will be influenced by leadership style and communication while the remaining 8.5% performance variables are influenced by other variable. The results of the F test show that leadership and communication styles simultaneously have a significant effect on employee performance because F-test has greater that F-table 172.631 and the value of significance is 0.00. While the results of the t-test for leadership style variables are obtained by t-test greater than t-table that is 6.803 > 2, this means that leadership styles have a significant effect on employee performance, and for communication variables has value of t-test greater than t-table are 5.159> 2.037 so communication has as partially has significant effect on employee performance Keywords: Leadership style, Communication and Performance